2005
DOI: 10.22621/cfn.v119i4.190
|View full text |Cite
|
Sign up to set email alerts
|

Travel Rates of Wolves, <em>Canis lupus</em>, in Relation to Ungulate Kill Sites in Westcentral Alberta

Abstract: . 2005. Travel rates of Wolves, Canis lupus, in relation to ungulate kill sites in westcentral Alberta. Canadian Field-Naturalist 119(4): 573-577.Recent advancements in Global Positioning Systems (GPS) radiocollar technology permit analysis of fine-scale animal movements. We used concurrent aerial and GPS monitoring to determine winter travel rates of Wolves (Canis lupus) in relation to ungulate kill sites in managed forest landscapes in westcentral Alberta. Wolves preyed predominately on Moose (Alces alces) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The importance of deer to Wolves in this study area should not be underestimated. Kuzyk et al (2005) found Wolves in this study area traveled 4.2 times less when near ungulate carcasses then when away from them, and suggested that Wolf packs preying primarily on deer, as opposed to Moose, may pose a greater predation risk to Caribou due to associated increase travel and encounter rates. Further research to quantify the importance of deer in this Wolf-ungulate system should be initiated such as measuring Wolf encounter rates with deer (Kunkel et al 2004).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The importance of deer to Wolves in this study area should not be underestimated. Kuzyk et al (2005) found Wolves in this study area traveled 4.2 times less when near ungulate carcasses then when away from them, and suggested that Wolf packs preying primarily on deer, as opposed to Moose, may pose a greater predation risk to Caribou due to associated increase travel and encounter rates. Further research to quantify the importance of deer in this Wolf-ungulate system should be initiated such as measuring Wolf encounter rates with deer (Kunkel et al 2004).…”
Section: Discussionmentioning
confidence: 67%
“…The larger Wolf packs (Lynx Creek n = 18; Simonette n = 11) preyed primarily on Moose, whereas the smallest pack (Prairie Creek n = 5) preyed predominately on deer, consistent with results from other nearby studies (Carbyn 1974;Weaver 1994). A confounding factor in estimating numbers of Wolf-killed ungulates in west-central Alberta is the difficulty of detecting Wolf-killed deer (Kuzyk 2002;Kuzyk et al 2005), due to the small size and cryptic color of deer, and the short time required for Wolves to consume deer carcasses (Fuller 1989). All Wolf packs in this study were observed either hunting deer or at deer kills.…”
Section: Discussionmentioning
confidence: 99%